Does family planning counselling during health service contact improve postpartum modern contraceptive uptake in Ethiopia? A nationwide cross-sectional study - Mruts, Kalayu Brhane; Tessema, Gizachew; Dunne, Jennifer; Gebremedhin, Amanuel; Scott, Jane; Pereira, Gavin (BMJ PUBLISHING GROUP, 2022)
OBJECTIVE: This study examined the association between family planning counselling receipt during the 12 months preceding the survey and postpartum modern contraceptive uptake in Ethiopia. We hypothesised that receiving family planning counselling either within the community setting by a field health worker or at a health facility by a healthcare attendant during the 12 months preceding the survey improves postpartum modern contraceptive uptake. DESIGN: We used a cross-sectional study of the Ethiopian Demographic and Health Survey conducted in 2016.Ethiopia. PARTICIPANTS: A total of 1650 women who gave birth during the 12 months and had contact with service delivery points during the 12 months preceding the survey. PRIMARY OUTCOME: A weighted modified Poisson regression model was used to estimate an adjusted relative risk (RR) of postpartum modern contraceptives. RESULTS: Approximately half (48%) of the women have missed the opportunity to receive family planning counselling at the health service contact points during the 12 months preceding the survey. The postpartum modern contraceptive uptake was 27%. Two hundred forty-two (30%) and 204 (24%) of the counselled and not counselled women used postpartum modern contraceptive methods, respectively. Compared with women who did not receive counselling for family planning, women who received counselling had higher contraceptive uptake (RR 1.32, 95% CI 1.04 to 1.67). CONCLUSION: Significant numbers of women have missed the opportunity of receiving family planning counselling during contact with health service delivery points. Modern contraceptive uptake among postpartum women was low in Ethiopia. Despite this, our findings revealed that family planning counselling was associated with improved postpartum modern contraceptive uptake.